Effects of land use changes on livelihood pattern of small farmers - Mondal, Gautam (BRAC University, 2010)
In Bangladesh, the livelihood of rural people is dependent largely on agricultural activities but only the paddy production in small pieces of land is not sufficient to satisfy the needs for survival of the small farmers. So they started thinking about the alternative use of lands in order to get increased output from there small pieces of land and found a new way of using their scarce resource in mixed nature. As the same piece of land is used for two or more different productive purposes in a single year these changes in land use have effects on livelihood pattern largely in employment pattern, income, seasonality, social identity etc. This study identified the issues on how the livelihood pattern of the small farmers has changed with the changes of land use.